449 Safety and health: building injury prevention into the healthcare system. (1st September 2016) - Cohen, Larry; Davis, Rachel
Abstract : Background (issue/problem): Beyond the direct deleterious toll on individuals, injury incurs high costs to the healthcare sector and increases the risk of other poor health outcomes, such as chronic illness and poor mental wellbeing. The healthcare sector can play important roles in injury prevention, not only by treating injured patients, but also by addressing the community conditions that increase the risk for injury. In order to build injury prevention into the healthcare system, healthcare organisations can benefit from models that bridge community prevention and health service delivery. Objective: In this session, participants will learn about Prevention Institute's Community-Centred Health Home (CCHH) model to promote systems change and active involvement in community advocacy. The vision of a community-centred health home takes models such as community oriented primary care and the medical home a step further by encouraging health care institutions to take an active role in strengthening their surrounding community. Results: When a Chinatown resident was struck and killed by a car while crossing the street in Oakland, California, Asian Health Services (AHS) staff became aware of pedestrian safety as a health issue in their community. AHS engaged in the CCHH steps of inquiry, analysis, and action and collaborated with several community groups, business owners, and city planning agencies to instal a "scramble" crosswalk to stop vehicle traffic and allow pedestrians to safely cross in all directions. Early data showed the "scramble" reduced car-pedestrian incidents by as much as fifty percent. A larger community transportation and planning project also emerged out of the coalition to further address environmental factors impacting pedestrian safety. Conclusions: The CCHH model is being piloted in several states in the United States. The model can be applied in other counties to advance the integration of injury prevention into the healthcare system.